Coupling Between Magmatic Degassing and Volcanic Tremor in Basaltic Volcanism - Salerno, Giuseppe G.; Burton, Mike; Di Grazia, Giuseppe; Caltabiano, Tommaso; Oppenheimer, Clive (Frontiers in Earth Science, 2018)
Magmatic degassing, typically measured as SO2 flux, plays a key role in controlling volcanic eruption style and is one of the key parameters used by volcano observatories to assess volcanic unrest and detect eruption precursors. Volcanic tremor, the integrated amplitude of seismic energy release over a range of frequencies, is also a key parameter in volcano monitoring. A connection between volcanic degassing and tremor has been inferred through correlations between the signals which are often, but not always, observed during periods of unrest or eruption. However, data are often equivocal and our understanding of the physical processes, which couple degassing with tremor are still evolving. New insights into degassing-tremor coupling can be made by investigation of the long-term relationship between degassing and tremor, focussing on the frequency-dependence of tremor and passive degassing behaviour. In this study, we examine how long-term SO2 emission rates and volcanic tremor on Mt. Etna, track rapid variability in eruptive dynamics. Correlations between SO2 flux and tremor are explored in both quiescent and eruptive periods, comparing the two parameters at both long and short time-scales (<< 1 day) for ~2 years. Our analysis reveals that over month-long timescales passive degassing of SO2 and tremor tend to be well-correlated, but these correlations are lost over shorter timescales. This reflects a coupling process between passive degassing and tremor, produced by a combination of gas flow through permeable magma and the convective flow of magma within the conduit. Short-term correlations are lost because variations in the continuous degassing process are relatively small compared with the overall degassing rate and fall below measurement noise..During eruptive periods strong correlations are observed between degassing and tremor, with a greater contribution of higher frequency signal in tremor, controlled by eruptive style. These observations suggest that in sin-eruptive periods the tremor source is dominated by the coupling between the eruption column and the ground through infrasonic waves, rather than conduit processes. Our results demonstrate the importance of high quality long-term observations and offer new insights into the physical mechanisms which couple degassing and volcanic tremor at active volcanoes.